Analisis Perbandingan Algoritma Argon2id Dan Bcrypt Berbasis Cia Triad Dengan Python - Hazri Agung Endarya; Evy Nurmiati (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
Password security is a critical component of modern information systems. This study analyzes and compares the bcrypt and Argon2id hashing algorithms using the Python programming language within the CIA Triad (Confidentiality, Integrity, Availability) framework. A quantitative-experimental approach was applied by testing ten varying password samples using bcrypt's cost factor of 12 and Argon2id's parameters with 65,536 KB of memory, 3 iterations, and 4 parallelism. The test results show that both algorithms produce fixed-length output and a random salt mechanism that effectively prevents rainbow table attacks. In terms of performance, Argon2id is more efficient, with an average hashing time of 89–121 ms compared to bcrypt's 207–224 ms. Argon2id also excels in confidentiality due to its memory-hard nature, which complicates GPU- and ASIC-based attacks. Overall, Argon2id is recommended for systems with high security requirements, while bcrypt remains relevant in memory-constrained environments.